Pengaturan Perjanjian Pengikatan Jual Beli Atas Rumah Tempat Tinggal Oleh Warga Negara Asing Dengan Berlakunya Peraturan Menteri Agraria Dan Tata Ruang Nomor 29 Tahun 2016 - Jayanti, Made Utami (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018), 2018)
The enactment of Minister of Agrarian and Spatial Planning Number 29 of 2016 concerning Procedures for Granting, Releasing, or Transferring the Right to Ownership of Residential Houses by Foreigners Domiciled in Indonesia has not sufficiently accommodated the interests of Foreign Citizen while in Indonesia. This is evidenced by the lack of sufficient rules to protect the interests of foreign national while implementing a sale and purchase agreement on ownership of a residence during their domicile in Indonesia. This research is a normative legal research. Normative legal research consists of statute approach and legal concepts. The legal material collection technique was by using snowball techniques. The results of the study show that the regulation of residential property that can be owned by foreign nationals while domiciled in Indonesia is not sufficient to provide legal protection for foreign nationals in the event of losses, which require foreigners to pay for the shortage of the nominal purchase of a residential house due to the transition of legislation. The importance of establishing new legislation regarding the ownership of housing by foreigners during their domicile in Indonesia as an effort to realize legal protection for foreign nationals who have contributed to the development of the national economy. The Indonesian government should immediately make or amend the laws and regulation concerning the ownership of houses by foreigners. This must be done so as not to reduce the trust of foreign nationals to invest in Indonesia, which will certainly have an impact on the national economy.